Implementasi Religious Culture Pada Pembelajaran Pendidikan Agama Islam di Madrasah - Rofiqoh, Nur Indah; Afrianti, Dwi; Syarqawi, Abdullah (Proceedings of Annual Conference for Muslim Scholars, 2024)
Madrasahs prioritize both cognitive and experiential learning, fostering religious culture to instill positive behaviors through values, activities, and symbols. This study aimed to identify religious cultural values in Islamic religious education at Madrasah Aliyah. Using a qualitative field study approach, data was collected through observation, interviews, and documentation. Data analysis involved data collection, reduction, presentation, and verification. The study found that religious culture in Madrasah Aliyah manifests in mutual respect, tolerance, congregational prayers, Quran memorization, and joint Islamic holiday activities. The curriculum implementation is consistent across the three madrasas studied. The implications of these values are significant, impacting the entire academic community, particularly students.